Developmental hematopoiesis: ontogeny, genetic programming and conservation. - Ciau-Uitz, A; Monteiro, R; Kirmizitas, A; Patient, R (Elsevier, 2014)
Hematopoietic stem cells (HSCs) sustain blood production throughout life and are of pivotal importance in regenerative medicine. Although HSC generation from pluripotent stem cells would resolve their shortage for clinical applications, this has not yet been achieved mainly because of the poor mechanistic understanding of their programming. Bone marrow HSCs are first created during embryogenesis in the dorsal aorta (DA) of the midgestation conceptus, from where they migrate to the fetal liver and, eventually, the bone marrow. It is currently accepted that HSCs emerge from specialized endothelium, the hemogenic endothelium, localized in the ventral wall of the DA through an evolutionarily conserved process called the endothelial-to-hematopoietic transition. However, the endothelial-to-hematopoietic transition represents one of the last steps in HSC creation, and an understanding of earlier events in the specification of their progenitors is required if we are to create them from naïve pluripotent cells. Because of their ready availability and external development, zebrafish and Xenopus embryos have enormously facilitated our understanding of the early developmental processes leading to the programming of HSCs from nascent lateral plate mesoderm to hemogenic endothelium in the DA. The amenity of the Xenopus model to lineage tracing experiments has also contributed to the establishment of the distinct origins of embryonic (yolk sac) and adult (HSC) hematopoiesis, whereas the transparency of the zebrafish has allowed in vivo imaging of developing blood cells, particularly during and after the emergence of HSCs in the DA. Here, we discuss the key contributions of these model organisms to our understanding of developmental hematopoiesis.